2016
DOI: 10.1016/j.envsci.2015.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Redefining maladaptation

Abstract: As experiences of implementation of climate change adaptation are accumulating, there is a need to increase the understanding of negative effects that might occur and the capacity to assess them. Maladaptation in this context has remained elusively defined and sparingly used, and therefore difficult to apply. Based on a literature review, we identify the conceptual boundaries of maladaptation, assess how it can be used to analyse negative effects of adaptation policies and measures and propose a typology of ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
191
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(192 citation statements)
references
References 44 publications
0
191
0
1
Order By: Relevance
“…In addition, power to was associated with leadership in several papers, such as the leadership of a committed politician in bringing about climate change adaptation or the local leadership of a community (e.g., Charles, ; Chu, Anguelovski, & Carmin, ). In connection with this, collaborative agency was related to the dimension of power to , seen in influential networks or in alliances formed to influence political decision‐making (e.g., Dodman & Mitlin, ; Eriksen & Lind, ), strategic collaboration across political levels (e.g., Vedeld, Coly, Ndour, & Hellevik, ), or networks (e.g., Newsham & Thomas, ; Petzold, ; Vignola, McDaniels, & Scholz, ) or through forming alliances to facilitate learning (e.g., Broto, Boyd, & Ensor, ; Schmid, Knierim, & Knuth, ), share tasks (e.g., Klein, Mäntysalo, & Juhola, ), or link knowledge with institutional support (e.g., Broto et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, power to was associated with leadership in several papers, such as the leadership of a committed politician in bringing about climate change adaptation or the local leadership of a community (e.g., Charles, ; Chu, Anguelovski, & Carmin, ). In connection with this, collaborative agency was related to the dimension of power to , seen in influential networks or in alliances formed to influence political decision‐making (e.g., Dodman & Mitlin, ; Eriksen & Lind, ), strategic collaboration across political levels (e.g., Vedeld, Coly, Ndour, & Hellevik, ), or networks (e.g., Newsham & Thomas, ; Petzold, ; Vignola, McDaniels, & Scholz, ) or through forming alliances to facilitate learning (e.g., Broto, Boyd, & Ensor, ; Schmid, Knierim, & Knuth, ), share tasks (e.g., Klein, Mäntysalo, & Juhola, ), or link knowledge with institutional support (e.g., Broto et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Maladaptation is defined by Juhola et al () as “intentional adaptation policy or measure directly increasing vulnerability for the targeted and/or external actor(s), and/or eroding preconditions for sustainable development by indirectly increasing society's vulnerability”.…”
mentioning
confidence: 99%
“…Recent scholarship has however shown that REDD+ can also lead to potentially negative experiences for local communities (Sunderlin, Ekaputri, et al, 2014;, which can in turn lead to the possibility of 'maladaptive' practices (Juhola et al, 2016). Enabling the emergence of a strategy for REDD+ that would incorporate and maximize adaptation would reduce the risk of maladaptive practices.…”
Section: Enabling Adaptation: Towards Implementing a Redd+ Strategymentioning
confidence: 99%
“…The complexity of recognising how to achieve this is a direct result of understanding the underlying processes of society that are related to adaptation (Eriksen et al, 2015;Termeer et al, 2015). This is challenging and characterised by uncertainty and if done incorrectly can cause maladaptations (Adger et al, 2005b;Barnett & O'Neill, 2010;Juhola et al, 2016).…”
Section: Adaptation As a Multi-scalar Phenomenonmentioning
confidence: 99%
“…Maladaptation has historically not been a widely-used concept in climate change research, but since 2010, a literature on empirical examples of maladaptive outcomes has emerged . Juhola et al (2016) identified three types of maladaptive outcomes from empirical examples: (i) rebounding vulnerability implies that an adaptation action increases the climate vulnerability of the implementing or targeted actor; (ii) shifting vulnerability implies that an adaptation action increases climate vulnerability for one or several external actors; and (iii) eroding sustainable development is when an adaptation action has negative impacts on environmental, social, and/or economic conditions. Based on the previous definitions and interpretations of the concept, Juhola et al (2016, p. 139) defined maladaptation as 'a result of an intentional adaptation policy or measure directly increasing vulnerability for the targeted and/or external actors, and/or eroding preconditions for sustainable development by increasing society's vulnerability'.…”
Section: Operational Definitionsmentioning
confidence: 99%